Potential of renewable resources in Romania and the EU - Petruta Turek-Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
In most European countries in the energy sector, a reconsideration of renewable energy priorities is taking place, increasing consumer safety and protecting the environment through the use of renewable energy sources that provide an affordable and guaranteed solution in the medium and long term. In Romania renewable energy constitutes 30% of the total percentage of energy used, although we have a high potential of renewable energy sources such as biomass, hydro or wind energy. In order for renewable energy sources to become an important factor in mitigating climate change and improving the overall energy security of the European Union, it is necessary to change the way renewable energies are promoted within EU Member States.
Keywords: Q4; Q40; Q42; Q43; Q47; Q49; 330; biomass; green energy; wind energy